Product pricing based on customer perception quality and service convenience using interval type-2 fuzzy logic system - Purnomo, Muhammad Ridwan Andi; Saputro, Iswoyo Seno (Universitas Ahmad Dahlan, 2024)
In the competitive landscape of customer goods, particularly in the wrapping paper industry, pricing strategies are critical to achieving market success. This study presents a novel approach to product pricing by integrating customer perception quality and service and convenience factors using interval type-2 fuzzy logic system (IT2FLS). The customer perception quality factor is subdivided into material quality and aesthetics design sub-factors while the service and convenience factor comprise web-based ordering system as well as the web-based post-sale customer engagement. The methodology involves collecting data through customer surveys and expert evaluations to quantify the perceived importance and performance of each sub-factor. The IT2FLS is employed to handle the inherent uncertainty and imprecision in experts’ judgment, providing a robust framework for aggregating these qualitative assessments into a comprehensive pricing model. This IT2FLS allows for the dynamic adjustment of pricing based on fluctuating customer perceptions and service levels. The outcome of the proposed IT2FLS is a pricing factor that serves as a multiplier for the standard product price established by the company. The new product prices have been validated also considering historical data and it was found that the prices remain acceptable to customers without drastically impacting sales. This study contributes to the body of knowledge on pricing strategies by offering a sophisticated, mathematically grounded approach that accounts for the complex, fuzzy nature of customer preferences. The proposed model not only enhances pricing accuracy but also provides a flexible tool for managers to adapt pricing strategies in real-time based on customer feedback and service performance.